Myocardial infarction centres: the way forward. (25th May 2005) - Andersen, H R; Terkelsen, C J; Thuesen, L; Krusell, L R; Kristensen, S D; Bøtker, H E; Lassen, J F; Nielsen, T T
Abstract : In the era of primary PCI, a strategy of admitting patients to the nearest hospital should be obsolete. Instead, a prehospital diagnostic strategy should be implemented in order to: (1) refer patients directly to interventional centres, thereby eliminating delay at local hospitals; (2) alert the interventional centre, thereby reducing door to balloon times; (3) initiate adjunctive medication in the prehospital phase